Evidence-based veterinary nursing – it's more sexy than you might think!. Issue 3 (4th March 2017) - Macdonald, Jill; Buckley, Louise; Mann, Alison
Abstract: Evidence-based veterinary medicine is a concept that is increasingly integral to the practice of veterinary nursing. This article was based on the experiences of three recipients of a veterinary nursing bursary to attend the Veterinary Evidence conference this year as they learnt how important it is to develop the skill set needed to review the evidence and apply it to clinical practice. Support for nurses to develop these skills is widely available and RCVS Knowledge, in particular, provides a range of resources – from conferences and workshops to guides and online CPD tools – that nurses are encouraged to take advantage of.